2014
DOI: 10.1080/10498850.2012.741188
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Compositions and Antioxidant Activities of a Specialty Aquatic VegetableNymphoides hydrophyllain Taiwan

Abstract: Nymphoides hydrophylla (NH), a lesser known aquatic vegetable, is a popular dish among the Hakka community in Taiwan. This study aimed to examine the proximate and polyphenolic compositions of NH and evaluate its antioxidant activities using various antioxidant assays. Results showed that the moisture, crude protein, crude fat, carbohydrate (crude fiber), and ash contents of fresh NH were 89.46, 0.46, 0.47, 4.11 (3.65), and 5.50%, respectively. In the antioxidant studies, the NH ethanolic extract (NH-E) exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In addition it is reported that the polyphenolic as well as flavonoids content in the ethanolic extract is greater than that in the aqueous extract explaining its greater antioxidant influence, yet, according to the HPLC analysis the superior content of flavonoids (2.8 times ) particularly quercetin and kaempferol in addition the polyphenolic content (1.6 times) in the ethanolic extract as compared to the aqueous extract explains the reported antioxidant effect. Thus, the magnitude of the antioxidant influence is attributed to the quantity and quality of the polyphenolic compounds in particular kaempferol and quercetin [270] .…”
Section: Nymphoides Aquatic Plants Species Polyphenolic and Flavonoid...mentioning
confidence: 99%
“…In addition it is reported that the polyphenolic as well as flavonoids content in the ethanolic extract is greater than that in the aqueous extract explaining its greater antioxidant influence, yet, according to the HPLC analysis the superior content of flavonoids (2.8 times ) particularly quercetin and kaempferol in addition the polyphenolic content (1.6 times) in the ethanolic extract as compared to the aqueous extract explains the reported antioxidant effect. Thus, the magnitude of the antioxidant influence is attributed to the quantity and quality of the polyphenolic compounds in particular kaempferol and quercetin [270] .…”
Section: Nymphoides Aquatic Plants Species Polyphenolic and Flavonoid...mentioning
confidence: 99%
“…NH contains crude fat, protein, carbohydrate, fiber, etc., along with gallic acid, catechin, ferulic acid, etc. Its useable parts are leaves and stalks, which are pulverized with oil and used for various purposes 18,19,20 .…”
mentioning
confidence: 99%